Adjective forms and functions in British English child-directed speech. Issue 1 (24th January 2020) - DAVIES, Catherine; LINGWOOD, Jamie; ARUNACHALAM, Sudha
Abstract: Adjectives are essential for describing and differentiating concepts. However, they have a protracted development relative to other word classes. Here we measure three- and four-year-olds' exposure to adjectives across a range of interactive and socioeconomic contexts to: (i) measure the syntactic, semantic, and pragmatic variability of adjectives in child-directed speech (CDS); and (ii) investigate how features of the input might scaffold adjective acquisition. In our novel corpus of UK English, adjectives occurred more frequently in prenominal than in postnominal (predicative) syntactic frames, though postnominal frames were more frequent for less-familiar adjectives. They occurred much more frequently with a descriptive than a contrastive function, especially for less-familiar adjectives. Our findings present a partial mismatch between the forms of adjectives found in real-world CDS and those forms that have been shown to be more useful for learning. We discuss implications for models of adjective acquisition and for clinical practice.